‘I fear only the neighbourhood and the Lord!’: Youth violence in marginalized spaces - Kurtenbach, Sebastian (European journal of criminology, 2023)
Male juveniles in segregated poor neighbourhoods are at increased risk of violence. The code of the street approach is commonly used to understand the context informing street violence in such marginalized spaces, but the concept is mainly used in Western countries, especially in African American communities in the US. This study investigates whether the code of the street is also applicable to the largest Roma neighbourhood in Europe, located in Bulgaria, through guided interviews with male juveniles. The results show that some elements of the code work are applicable in this space, but clear differences also emerge. These findings affect the generalizability of the approach and the understanding of street violence.